Teaching Character in the 21st Century: Lessons from Surat Al-Jumu'ah Ayat 2 for Educational Reform - Nadri Taja; Nabilah Nuraini (Masagi: Jurnal Pendidikan Karakter, 2025)
Surah Al-Jumu'ah, Verse 2, provides a deep understanding of the purpose of education in Islam, which focuses not only on intellectual knowledge but also on the purification of the soul (tazkiyah) and the teaching of wisdom. This verse teaches important principles in character education that are relevant to the challenges of education in the 21st century, where the formation of holistic individuals, encompassing moral, spiritual, and intellectual aspects, is a primary need. This study uses a qualitative approach with a literature study method to analyze the influence of Surah Al-Jumu'ah, Verse 2, on character education. The sources used include books, journal articles, and academic references relevant to the theme of character education and learning theories. The main findings indicate that Surah Al-Jumu'ah, Verse 2, can be used as a basis for character education reform in the 21st century by integrating three main aspects: knowledge and deeds, holistic education encompassing spiritual and moral aspects, and strengthening social responsibility. The values contained in this verse offer an inclusive and relevant approach to pluralistic global education, helping students develop not only academically but also morally and ethically. Further discussion shows that the implementation of these principles can shape a generation that is more responsible, ethical, and ready to face global challenges with integrity.